Hospital nurses' knowledge about older patients in Turkey: a validation and comparison study - Deniz Harputlu; Sander Kerstens; Funda Özdemir; Jeroen Dikken (BMC, 2022)
Abstract Background In Turkey, nursing care in hospitals has gradually included more older patients, resulting in a need for knowledgeable geriatric nurses. It is unknown, however, whether the nursing workforce is ready for this increase. Therefore, the aim of this study is to validate the Knowledge about Older Patients Quiz (KOPQ) in the Turkish language and culture, to describe Turkish hospital nurses' knowledge about older patients, and to compare levels of knowledge between Turkish and Dutch hospital nurses. Method First, the KOPQ was translated, resulting in the KOPQ-TR. Then, content validity was assessed by 10 geriatric experts using the Lynn method, a pilot test among 10 nurses was conducted, and a Rasch analysis was performed using data from 135 nurses working in two Turkish hospitals. Finally, a comparison between Turkish and Dutch nurses' levels of knowledge was performed. Results The results of the qualitative validation (i.e., content validity by experts and nurses), model fit, item reliability and the item separation index of the KOPQ-TR proved excellent, indicating good content and construct validity. However, the Person Separation Index and Person Reliability of the Rash analysis did not meet the criteria for adequate scale and psychometric validation. The levels of knowledge among Turkish nurses were significantly lower than those of Dutch nurses. Conclusions The KOPQ-TR is promising for use in Turkey, although psychometric validation should be repeated using a better targeted sample with a larger ability variance to adequately assess the Person Separation Index and Person Reliability. Currently, education regarding care for older patients is not sufficiently represented in Turkish nursing curricula. However, the need to do so is evident, as the results demonstrate that knowledge deficits and an increase in older patients admitted to the hospital will eventually occur. International comparison and cooperation provides an opportunity to learn from other countries that currently face the challenge of an aging (hospital) population.